Política de educação especial na perspectiva inclusiva e formação continuada de professores da Rede municipal de educação de São Paulo: entre apropriações e práticas - Orlandin, Barbara De Souza [UNIFESP] (2020)
This qualitative research aimed to understand and analyze the policy of continuing education for Special Needs Education in its macro and micro contexts, mobilizing the policy cicle approach developed by Stephen Ball in its five contexts: influence, text production, practice, results and policy strategy. A brief historical rescue on Special Education and teacher training in Brazil was started, identifying trends and historical influences on current policies. The approach to the micro contexts was based on the choice of the Municipal Education Network of São Paulo (RME-SP) and, later, the Center of Formation and Accompaniment to the Inclusion in the Region of São Miguel Paulista (CEFAI-MP) as the locus of the research. We analyzed the legislative texts referring to Special Education and Continuing Education in the municipality of São Paulo, as well as the formative actions carried out by the Municipal Secretary of Education (MSE) division responsible for Special Education. Within the context of the practice, semi-structured interviews were conducted with the coordinator of CEFAI-MP and with two Support and Accompaniment Teachers for Inclusion. It also counted on the application of a questionnaire of closed and open questions to teachers of four schools belonging to the region of São Miguel Paulista. The questionnaires were answered by 32 teachers. All the data were analysed in the light of the concepts of politics as text and speech for the legislative analyses, the concepts of power and speech by Michel Foucault and the concepts of strategies and tactics by Michel de Certeau. The path traced out allowed us to understand that the discourse of education for all adopted by international organizations entered Brazil via educational reforms that took place in the 1990s. In the Special Education plan, it found its modus operandi in the so-called inclusive paradigm, by affirming the insertion of these students in regular schools. In this context, the movement of teaching universitarization occurred, which has been offered in a light way. Continued training has gained greater prominence in view of the initial training given the economy of the public coffers and the possibility of realigning teaching to the precepts of policies. The CEFAI-MP, implemented in the RME-SP in 2004, has since then been active in teaching training and monitoring the work done in schools. It has been seen that the current emphasis on Specialist Educational Care present in national policy has been adjusted by local policy, and this has generated greater distance among Specialist Education teachers from regular classes. Teachers are aware of the importance of this teacher, but said there was little articulation between this service and the regular classroom. The RME-SP has continued in-service and out-of-service training offered by the Cefais and the MSE directly and via private-sector partnerships. However, it was found that teachers have been unable to participate in the training, having little impact on their daily work. The data from the questionnaires revealed weaknesses throughout the Special Education and Continuing Training Policy of the RME-SP. The female teachers working in CEFAI-MP revealed speeches congruent with those stated in the policy as text, emphasizing teachers as responsible for inclusion. However, by revealing precarious working conditions, teachers raised issues that make the success of the so-called inclusive policy in the RME-SP impossible.